Using SQLite - Kreibich, Jay A. (O'Reilly Media, 2011)
Application developers, take note: databases aren't just for the IS group any more. You can build database-backed applications for the desktop, Web, embedded systems, or operating systems without linking to heavy-duty client-server databases such as Oracle and MySQL. This book shows you how to use SQLite, a small and lightweight relational database engine that you can build directly into your application.